Prevalence of Non-Communicable Diseases and Social Interactions in Kenya: An Empirical Analysis - Mwai, Daniel (European Scientific Journal, ESJ, 2016)
Despite a remarkable progress in the control and management of communicable diseases over the past century, the world is not better-off as the prevalence of Non-Communicable Diseases (NCD) is on the increase, both in developed and developing countries. The upsurge in NCD prevalence is attributable to risk factors both outside and within the control of individuals. . One risk factor that has received less attention than it deserves is the social interactions variable. Social interactions are the established relationships among individuals, e.g., among peers or persons in the same circumstances. Interactions of persons in the same circumstances affect behavior because of the necessity for the individual to conform to established group norms or values. It is believed that NCD prevalence in Kenya is high in sections of the populations where social interactions among certain groups is intense, but little evidence exists in support of this supposition. This paper examines this assumption taking into account the endogeneity of behavior in a group setting .In particular, we estimate a binary probit model of an individual contracting a non-communicable disease, conditional on engaging in certain consumption behaviors that are malleable by peer or group pressure. The key finding from the estimation exercise is that variables that capture social interactions such as the village level means of drinking alcohol, consuming vegetables and fruits, and smoking cigarettes are significantly associated with the likelihood of getting an NCD. The policy implication of this finding is that NCD prevalence in Kenya can be reduced by implementing programs to change health behaviors within social groups.